Students' English Competence, Transformative Thinking, Creativity, and Work Readiness in the Gig Economy Era - Afifah, Wiwiek; Soeharto, Soeharto; Somae, Erik Tauvani; Kurniawan, Muhammad Hafiz; Maftukhin; Ahdiani, Ulaya (Institut Agama Islam Negeri Madura, 2025)
Abstract: As the gig economy era reshapes the global workforce, job readiness demands more than technical skills. Therefore, transformative thinking, creativity, and English competence become crucial. This study aims to explore how students from various backgrounds perceive the importance and the role of English competence, transformative thinking, and creative thinking in the gig economy era. Furthermore, this study also analyzes the relation between students’ socioeconomic background and their level of English competence toward their job readiness. Using a descriptive qualitative approach, data were collected through a reflective instrument based on open-ended questions designed to explore students’ views and strategies in facing the challenges of the gig economy era. Fifty-one students with different characteristics, including high and low achievers and socioeconomic backgrounds, volunteered for the study. Thematic analysis was used to identify mindsets and work readiness that emerged from their narratives. The findings revealed that English competence is strongly related to self-confidence, professional communication effectiveness, and the ability to build global connections. Meanwhile, transformative and creative thinking encourages students to think critically, adapt to change, design creative solutions, and think outside the box. Furthermore, developing work readiness requires motivation, engagement, and reflective thinking because these qualities enable students to adapt, learn, and perform well regardless of their financial situation.